INFORMATION SUPPORT FOR PRO-COMPETITIVE REGULATION OF THE SOCIALLY SIGNIFICANT REGIONAL MARKETS - V. Bobrova, Viktoriya; N. Korabeynikov, Igor; V. Kurlykova, Anna; S. Smotina, Olga (Gênero & Direito, 2020)
Purpose of the study: The purpose of this paper is to provide a theoretical underpinning and develop the information support for pro-competitive regulation of socially significant regional markets. Research methods: The study mainly employed the method of analyzing the content of Internet resources and quantitative evaluation of the obtained results. The study involved the analysis of 757 publications on major regional information resources regarding 15 types of priority and socially significant markets. Findings from the study. The paper suggests a method to evaluate publications on pro-competitive regulation of priority and socially significant markets on information resources available for businesses and consumers of products and services in the Orenburg region. The suggested method involved a comprehensive study of information openness of pro-competitive regulation of priority and socially significant markets and the assessment of rankings of priority and socially significant markets of Orenburg region by a set of indicators that were obtained through a survey of entrepreneurs and describe the state of the competitive environment. Conclusions. The paper presents information openness metrics for pro-competitive regulation of priority and socially significant markets. A disproportion was found in coverage of individual types of markets on Internet resources. The information resources were ranked by the level of activity in ensuring the information openness and availability of data on pro-competitive regulation of socially significant and priority markets for businesses and consumers of products and services. It is shown that the work toward information openness of pro-competitive regulation of priority and socially significant markets is inefficient. The paper has a practical value for specialists engaged in the competitive development of meso-economic market systems and professors of economics at higher education institutions